2007
DOI: 10.1016/j.juro.2007.07.121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Energy Devices for Vessel Sealing and Peripheral Energy Spread in a Porcine Model

Abstract: The LigaSure 5 was superior to the other devices tested regarding the ability to seal vessels up to 7 mm. The ACE is an efficient vessel sealing system with the ability to seal vessels up to 5 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
2
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 5 publications
8
87
2
7
Order By: Relevance
“…[16][17][18][19] However, both electrosurgical and ultrasonic devices have limitations, including the potential for undesirable charring and unnecessarily large collateral thermal damage zones. [20][21][22] For example, more thermal energy is required to seal large blood vessels with such devices, and stray thermal energy escaping the seal area can lead to unintended lateral tissue thermal damage.…”
mentioning
confidence: 99%
“…[16][17][18][19] However, both electrosurgical and ultrasonic devices have limitations, including the potential for undesirable charring and unnecessarily large collateral thermal damage zones. [20][21][22] For example, more thermal energy is required to seal large blood vessels with such devices, and stray thermal energy escaping the seal area can lead to unintended lateral tissue thermal damage.…”
mentioning
confidence: 99%
“…[7] The LigaSure ® vessel sealing system has shown to have shorter dissection time, better seal quality time, lesser blood loss, fewer conversion rates. [8][9][10] Moreover, the device claims to measure temperature or impedance to provide consistent heating in order to prevent injuries. [11] A study has revealed the sealing procedure to be as reliable as clips or ligatures.…”
Section: Discussionmentioning
confidence: 99%
“…14,24,25,26,27,28 However, for some of these devices, successful sealing of vessels >5 mm have not been reported. 21 Ultrasonic vessel sealing devices tend to produce less lateral thermal damage (1 to 1.9 mm), but require longer seal times (3.3 to 14 s), produce lower mean burst pressures (204 to 921 mmHg), and are limited to use on smaller vessels with <5 mm diameter.…”
Section: Discussionmentioning
confidence: 99%
“…13 Ultrasonic-based devices have been shown to produce less thermal spread than RF devices. 14,15 However, the active jaw of ultrasonic devices can reach temperatures in excess of 200°C (Refs. 15 and 16) and take >20 s to cool to usable temperatures.…”
Section: Energy-based Surgical Devicesmentioning
confidence: 99%